Place-making in Cajun Country: Laotians’ Lane Xang Village - Sisavath, Davorn (American Studies, 2023)
Set against Louisiana’s coastal south landscape and local distinctiveness, Lane Xang Village is home to Laotians who resettled with sponsorship from the Catholic Diocese in the 1970s and 1980s, and through secondary migration after learning of federally funded job training made available. Like many newly arrived Southeast Asian refugees in Louisiana’s Gulf Coast, Laotians landed job opportunities produced by the oil boom, while others filled the demand for unskilled labor in peeling shrimp, shucking oysters, picking peppers at the Tabasco factory, working in food processing, and garment factories. In their efforts to belong and stay, I argue place-making practices by Laotian refugees in Lane Xang village make visible their multiple displacements but also make evidence of their collective process to belong and endow their place with value and attachments.